Akuntabilitas Pengelolaan Alokasi Dana Desa (ADD) di Desa Panggungrejo, Kecamatan Kepanjen, Kabupaten Malang - Firsttantri Izza Aryanti; Dessy Putri Andini (Politeknik Negeri Jember, 2021)
This study aims to measure the application of the principle of accountability carried out by the Panggungrejo Village Government, Kepanjen District, Malang Regency in the management of Village Fund Allocation. This study used qualitative methods with data collection techniques used in the form of open interviews which were then followed by data validity testing using triangulation techniques. The results showed that all stages of Village Fund Allocation management carried out by the Panggungrejo Village Government had implemented the principle of accountability although there were obstacles experienced at the implementation stage, the cause of which was the delay in disbursing funds from the Malang Regency Government. Even so, the Panggungrejo Village Government has succeeded in implementing all indicators of conformity according to Peraturan Bupati Malang Nomor 35 Tahun 2017 at each stage. Keywords: Accountability, Village Fund Allocation, Village Government.